2016
DOI: 10.1038/srep25607
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived compounds stimulate the decomposition of organic matter in arctic permafrost soils

Abstract: Arctic ecosystems are warming rapidly, which is expected to promote soil organic matter (SOM) decomposition. In addition to the direct warming effect, decomposition can also be indirectly stimulated via increased plant productivity and plant-soil C allocation, and this so called “priming effect” might significantly alter the ecosystem C balance. In this study, we provide first mechanistic insights into the susceptibility of SOM decomposition in arctic permafrost soils to priming. By comparing 119 soils from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 48 publications
(63 reference statements)
5
76
0
Order By: Relevance
“…The positive legacy effect of field warming on respiration rates, months after thawed permafrost cores were recovered from the field, suggests that the observed warming effects may have been mediated indirectly through increased plant–soil transfer of labile carbon sources from root exudates. A comparison study on the effects of soil priming with labile C‐sources across four arctic sites in organic, mineral, and permafrost soils showed that especially mineral subsoils with low C‐content lose a relatively high proportion of their soil organic C during a 2‐week laboratory incubation (Wild et al., ). Their results suggest that microbial communities in the mineral layer are more strongly C‐limited and are especially vulnerable to soil C loss under a climate warming scenario, provided that plant root production will increase and lead to greater plant–soil C transfer to these deeper mineral soils.…”
Section: Discussionmentioning
confidence: 99%
“…The positive legacy effect of field warming on respiration rates, months after thawed permafrost cores were recovered from the field, suggests that the observed warming effects may have been mediated indirectly through increased plant–soil transfer of labile carbon sources from root exudates. A comparison study on the effects of soil priming with labile C‐sources across four arctic sites in organic, mineral, and permafrost soils showed that especially mineral subsoils with low C‐content lose a relatively high proportion of their soil organic C during a 2‐week laboratory incubation (Wild et al., ). Their results suggest that microbial communities in the mineral layer are more strongly C‐limited and are especially vulnerable to soil C loss under a climate warming scenario, provided that plant root production will increase and lead to greater plant–soil C transfer to these deeper mineral soils.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a previous study found weaker priming when the same amount of C was added in small, repeated doses than in one single dose (Qiao et al 2014), (2) it has been suggested that N mining is induced only by organic compounds in polymeric form that might promote a microbial community specialized on the breakdown of SOM polymers, whereas monomeric compounds such as glucose might promote a copiotrophic microbial community of limited depolymerization capacity (Fontaine et al 2003). Also in this case, microbial N mining would be connected to root litter production rather than to root exudation, which is dominated by monomeric compounds such as glucose ), (3) a stimulation of microbial N mining might also be restricted to the input of compounds that contain not only C, but also N. Although N addition often reduces SOC mineralization (which has been interpreted as a reduction in microbial N mining; Craine et al 2007;Phillips et al 2011), some studies show a stronger stimulation of SOC mineralization when both C and N are supplied (Chen et al 2014;Wild et al 2016), possibly since the added N can be used for enzyme synthesis (Allison et al 2009;Drake et al 2013). However, a stimulation of enzyme synthesis by N was not observed in this study (Table 2), and (4) finally, microbial N mining might depend on the association of plants with mycorrhizal fungi, an effect that we would have underestimated in our laboratory experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our hypothesis, we found that non-symbiotic soil microorganisms adjusted to a short-term increase in C availability not by accelerating the mobilization of N from SOM polymers such as proteins, but rather by using the already available N more efficiently. Considering that (1) C effects on microbial processes are typically restricted to soils of initially low C availability (e.g., Bengtson et al 2012;Wild et al 2016), and that (2) these soils are typically characterized by an excess of N, and by low N use efficiency (e.g., Mooshammer et al 2014a;Wild et al 2015; see also Supplementary Table S1), an increase in microbial N use efficiency might be a common adjustment to enhanced soil C availability and microbial N demand. Although our findings do not rule out that an increase in plant-soil C allocation, such as expected with rising atmospheric CO 2 concentrations and temperatures, can promote the release of available N from SOM polymers, they show that such an effect can be counteracted at least in the short term by an increase in microbial N use efficiency, reducing soil N availability and aggravating plant N limitation, but also mitigating soil N losses, e.g., by nitrate leaching and denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of vegetation, however, likely fueled microbial activity at depth, thus promoting decomposition of this more persistent C pool: we observed larger dissolved C and N pools at depth in vegetated mesocosms than in bare mesocosms (Figure S12), indicating downward transport of C. Also, microbial biomass C and N pools in the peat profile were significantly larger when vegetation was present (C: p = 0.006, N: p = 0.003, Figure S12; Table S9). The input of fresh, plant‐derived organics can lead to a positive priming effect, actively driving the decomposition of old organic matter (Kuzyakov, ) and GHG production at depth (Corbett et al, ; Voigt, Lamprecht et al, ; Wild et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, gaseous C production at depth is decoupled from soil surface C emissions, especially in peatlands (Blodau & Moore,): even if CO 2 and CH 4 production rates in or near the permafrost are high, gases can be consumed (reduction of CO 2 to CH 4 , oxidation of CH 4 to CO 2 ) while diffusing upwards through the soil profile (Dorodnikov, Marushchak, Biasi, & Wilmking, ). Further, downward leaching of nutrients and dissolved C from the surface and soil rooting zone to deeper soil layers can be an important process supporting microbial activity at depth (Corbett et al, ; Voigt, Lamprecht et al, ; Wild et al, ). All these processes determine whether permafrost thaw results in a net increase or decrease in ecosystem C emissions.…”
Section: Introductionmentioning
confidence: 99%